INTEGRASI PENDIDIKAN AGAMA DAN SAINS DI MADRASAH - Moh Farhan; Hidayatus Solihah; Samsudin Samsudin (Universitas Islam Sultan Agung, 2021)
This article explains the integration between religious education and science that occurs in Madrasah Aliyah Negeri 2 MAN, Kudus, based onboarding school Darul Adzkiya. The jargon